Implementasi Strategi Digital Marketing dan Manajemen Operasional pada UMKM 2Nailhouse Kota Batam - Windy Octaviana Manurung; Tiara Annisah; Intania Syafrina; Nina Pramita; Cristina Tan (STIE AMKOP, 2023)
MSMEs 2housenails is a business engaged in services that serves the installation and manufacture of false nails, nail art, pedicures, manicures, and also installation of false eyelashes. In this era, there are lots of target consumers who will use business services, such as those done by 2housenails MSMEs. However, not many business owners like this lack understanding in developing their business through digital marketing and business locations that are not strategic so that it can hinder operational management of the business. Therefore the writing of this article was carried out to provide knowledge development related to the smooth running of operational management which includes location strategy and digital marketing in MSMEs 2housenails by using the interview method with owners and consumers of MSMEs 2housenails and using the literature review method for material knowledge development. The result of writing this article is the achievement of physical and material implementation related to strategic location relocations and changes as well as additional knowledge related to digital marketing to expedite the operational management of MSMEs 2housenails. Keywords: Digital Marketing, Operational Management, MSMEs